UJI AKTIVITAS ANTIBAKTERI EKSTRAKDAUN KERSEN (Muntingia calabura L.) TERHADAP BAKTERI Staphylococcus aureus dan Methicillin-Resistant Staphylococcus aureus - Alfi Safitri; Eva Diansari Marbun; Denny Satria (Jurnal Farmanesia, 2019)
Kersen (Muntingiacalabura L) is one of the wild plants that have medicinal properties. Cherry leaves contain flavonoid compounds, alkaloids, tannins, saponins, and steroids/triterpenoids. This study aims to determine the antibacterial activity of cherry leaf extract (Muntingiacalabura L) against Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus. Dau cherry extract was prepared using the maceration method using 96% ethanol. The antibacterial activity was tested using the disc diffusion method. The results of the examination of the characteristics of the simplicia powder of cherry leaves obtained water content of 6.7%, water soluble extract content of 23.84%, marine ethanol content of 13.40%, total ash content of 1.61%, and acid insoluble ash content of 0.38%. Simplicia and cherry leaf extract contain flavonoids, alkaloids, tannins, sapomime, steroids/triterpenoids. Antibacterial activity test showed that cherry leaf extract (Muntingiacalabura L) inhibited the growth of Staphylococcus aureus at concentrations of 10% (13.7 mm), 20% (14.1 mm), 30% (15.0 mm), 40% (16, 0 mm), 50% (17.6 mm). Methicillin-Resistant Staphylococcus aureus bacteria at concentrations of extract 10% (13.5 mm), 20% (14.0 mm), 30% (14.8 mm), 40% (15.8 mm), 50% (17, 0mm). Cherry leaf extract has antibacterial activity against Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus bacteria.